The Safer Anaesthesia from Education (SAFE)® paediatric anaesthesia course: educational impact in five countries in East and Central Africa. (27th July 2019) - Boyd, N.; Sharkey, E.; Nabukenya, M.; Tumukunde, J.; Sipuka, N.; Zyambo, M.; Walker, I.; Hart, J.; Byrne‐Davis, L.
Summary: There is an urgent need to improve access to safe surgical and anaesthetic care for children living in many low‐ and middle‐income countries. Providing quality training for healthcare workers is a key component of achieving this. The 3‐day Safer Anaesthesia from Education (SAFE) ® paediatric anaesthesia course was developed to address the specific skills and knowledge required in this field. We undertook a project to expand this course across five East and Central African countries (Ethiopia, Kenya, Malawi, Uganda and Zambia) and train local faculty. This study reports the outcomes from course evaluation data, exploring the impact on knowledge, skills and behaviour change in participants. Eleven courses were conducted in a 15‐month period, with 381 participants attending. Fifty‐nine new faculty members were trained. Knowledge scores (0–50 scale) increased significantly from mean (SD) 37.5 (4.7) pre‐course to 43.2 (3.5) post‐course (p < 0.0001). Skills scores (0–10 scale) increased significantly from 5.7 (2.0) pre‐course to 8.0 (1.5) post‐course (p < 0.0001). One hundred and twenty‐six participants in Malawi, Uganda and Zambia were visited in their workplace 3–6 months later. Knowledge and skills were maintained at follow‐up, with scores of 41.5 (5.0) and 8.3 (1.4), respectively (p < 0.0001 compared with pre‐course scores). Content analysis from interviews with these participants highlighted positive behaviour changes in the areas of preparation, peri‐operative care, resuscitation, management of the sick child, communication and teaching. This study indicates that the SAFE paediatric anaesthesia course is an effective way to deliver training, and could be used to help strengthen emergency and essential surgical care for children as a component of universal health coverage.